Aplikasi Penyewaan Lapangan Futsal Berbasis Web - Fadhlurrahman, Muhammad Fatih Fahmi; Capah, Dwi Ade Handayani (Universitas Hamzanwadi, 2020)
In Indonesia, there is one well-known sport, namely Futsal. Therefore, there are many businesses such as futsal court rental places. Basically, the futsal field rental is still manual, that is, customers come to the futsal location and make field rental transactions. This manual futsal court rental has a problem, namely that prospective customers cannot immediately find out the available empty schedule, this causes when they are already at the location but there is no desired schedule they are just wasting time. The purpose of this research is to find a solution in order to solve the problem in the manual futsal court rental method. With the creation of a web-based futsal court rental application that is expected to be able to solve this problem. This application was created using the waterfall development method so that the process of making this application is recorded in order and neat. This study produces a web-based futsal court rental application that has been tested for its feasibility using the black box testing method. This application provides a field rental feature for potential customers, as well as facilitates the processing of field rental data and financial report data for field owners.